The tao of travel : enlightenments from lives on the road - Theroux, Paul. (England : Hamish Hamilton, 2011)
A collection of writings from Paul Theroux's fifty years of travel. Included are writings from other travelers such as Charles Dickens, Eudora Welty, Anton Chekhov, Ernest Hemingway and many others.
The importance of elsewhere -- Travel in brief -- The navel of the world -- The pleasures of railways -- Travel wisdom of Henry Fielding -- Murphy's rules of travel -- Travelers on their own books -- How long did the traveler spend traveling? -- Travel wisdom of Samuel Johnson -- The things that they carried -- Fears, neuroses, and other conditions -- Travelers who never went alone -- Travel wisdom of Sir Francis Galton -- Travel as an ordeal -- English travelers on escaping England -- When you're strange -- Travel wisdom of Robert Louis Stevenson -- It is solved by walking -- Travel feats -- Staying home -- Travel wisdom of Freya Stark -- Imaginary journeys -- Everything is edible somewhere -- Rosenblum's rules of reporting -- Travel wisdom of Claude Lévi-Strauss -- Perverse pleasures of the inhospitable -- Imaginary people -- Writers and the places they never visited -- Travel wisdom of Evelyn Waugh -- Travelers' bliss -- Classics of a sense of place -- Evocative name, disappointing place -- Travel wisdom of Paul Bowles. Dangerous, happy, alluring -- Five travel epiphanies -- The essential tao of travel.
Keywords: Travel -- Anecdotes; Travelers -- Anecdotes